Modalities of group A streptococcal prevention and treatment and their economic justification - Jeffrey W. Cannon; Rosemary Wyber (npj Vaccines, 2023)
Abstract Infection by group A Streptococcus (Strep A) results in a diverse range of clinical conditions, including pharyngitis, impetigo, cellulitis, necrotising fasciitis, and rheumatic heart disease. In this article, we outline the recommended strategies for Strep A treatment and prevention and review the literature for economic evaluations of competing treatment and prevention strategies. We find that most economic evaluations focus on reducing the duration of illness or risk of rheumatic fever among people presenting with sore throat through diagnostic and/or treatment strategies. Few studies have evaluated strategies to reduce the burden of Strep A infection among the general population, nor have they considered the local capacity to finance and implement strategies. Evaluation of validated costs and consequences for a more diverse range of Strep A interventions are needed to ensure policies maximise patient outcomes under budget constraints. This should include attention to basic public health strategies and emerging strategies such as vaccination.